Microstructure-Property Correlations for Hard, Superhard, and Ultrahard Materials - Kanyanta, Valentine (Springer International Publishing : Imprint: Springer, 2016)
This book discusses microstructure-property correlations and explores key microstructure features and how they affect the properties of a material. The authors discuss the effect of manufacturing and processing routes on microstructure and properties. They identify appropriate microstructure and mechanical characterization techniques essential for developing accurate microstructure-property relationships. The techniques include high resolution imaging methods and properties measurements such as hardness, strength, elastic modulus, and fracture toughness. Current and future trends in hard and superhard material design are revealed by the authors, including nanostructured materials, biomimicry, and novel manufacturing technologies.